DIGITAL SUKUK AND SHARIAH COMPLIANCE: A JURISPRUDENTIAL ANALYSIS OF BLOCKCHAIN INTEGRATION IN ISLAMIC FINANCE - Abubakar Muhammad Jibril; Inuwa Adamu; Souad Ezzerouali; Ummi Ibrahim Tafida; Mu'adil Faizin Faizin (Indonesian Scientific Journal of Islamic Finance, 2026)
This research examines the Shariah compatibility of blockchain-based sukuk instruments with a special emphasis on whether digitalization and distributed ledger technologies can be reconciled with Islamic legal requirements like risk-sharing, asset-backing, and the ban on riba and gharar. The article discusses whether blockchain facilitates or hinders the issuance and enforceability of Islamic financial instruments. A doctrinal and comparative legal qualitative approach was adopted. The study compared primary Islamic legal sources (Qur'an, Sunnah, fiqh), contemporary Shariah standards (e.g., AAOIFI), and case studies of blockchain sukuk in different jurisdictions, including the UAE and Indonesia. The research used thematic and jurisprudential analysis to examine compliance, gaps, and emerging regulatory concerns. The findings show Blockchain has the potential to facilitate Shariah-compliant sukuk if connected to real underlying assets and legitimate Islamic contracts. Smart contracts certainly automate ethical trades but need more robust asset linkage. There is compliance uncertainty because there are no global Shariah standards for tokenized ownership. Regulatory fragmentation across jurisdictions also undermines cross-border enforceability and investor confidence. A uniform regulatory and Shariah governance structure is the prerequisite for replicating blockchain sukuk on a global scale. Legal recognition, enforceability, and standardization of jurisprudence are the keys to unlock blockchain's full potential in Islamic finance. This study bridges classical Islamic legal theory and contemporary fintech innovation, offering a novel Shariah-centred examination of digital sukuk structures and operational challenges